2013
DOI: 10.1021/ja4012468
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Daptomycin by Cyclization via a Chemoselective Serine Ligation

Abstract: A total synthesis of daptomycin, the first natural product antibiotic launched in a generation, was achieved. This convergent synthesis relies on an efficient macrocyclization via a serine ligation to assemble the 31-membered cyclic depsipeptide. The difficult esterification by the nonproteinogenic amino acid kynurenine was accomplished via the esterification of a threonine residue by a suitably protected Trp ester, followed by ozonolysis. This synthesis provides a foundation and framework to prepare varied an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
132
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(141 citation statements)
references
References 52 publications
6
132
1
2
Order By: Relevance
“…153 On the other hand, different examples for the syntheses of cyclic peptides where the open-chain precursor is previously released from the resin to perform the macrocyclization in solution can also be found in the literature. 154 In nature, the biosynthetic macrocyclization reaction for the formation of macrocyclic peptides is catalyzed by a thioesterase domain at the C-terminal end of the assembly line. 155 However, release of the open-chain peptide for macrocyclization is also found in nature and it has been described, for example, for the imine macrocyclization of polypeptides at the C-terminal reductase domain of the respective nostocyclopeptide nonribosomal peptides that catalyzes the reductive release of the mature peptide chain.…”
Section: Experimental Aspects In the Synthesis Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…153 On the other hand, different examples for the syntheses of cyclic peptides where the open-chain precursor is previously released from the resin to perform the macrocyclization in solution can also be found in the literature. 154 In nature, the biosynthetic macrocyclization reaction for the formation of macrocyclic peptides is catalyzed by a thioesterase domain at the C-terminal end of the assembly line. 155 However, release of the open-chain peptide for macrocyclization is also found in nature and it has been described, for example, for the imine macrocyclization of polypeptides at the C-terminal reductase domain of the respective nostocyclopeptide nonribosomal peptides that catalyzes the reductive release of the mature peptide chain.…”
Section: Experimental Aspects In the Synthesis Ofmentioning
confidence: 99%
“…The reaction was performed at a range of concentrations from 5 to 50 mM, being the monomeric cyclic peptide the only observed product. 154 Most of the studies on the cyclization of peptides clearly reveal the importance of the exact peptidic sequence for the success of the macrocyclization. In the example reported in Figure 91, the change on one single amino acid (from Gly to Ala) made the cyclization unsuscessful.…”
Section: Conformational Preorganizationmentioning
confidence: 99%
“…The macrocyclization was effected by dissolving peptide salicylaldehyde ester (1072) in pyridine acetate buffer, followed by treating with TFA/H 2 O (Scheme 213). 337 3 References…”
Section: Daptomycin (1071) Is a Lipodepsipeptide Isolated Frommentioning
confidence: 99%
“…8 Lam et al recently reported the total synthesis of daptomycin. 9 They were unable to form the crucial ester linkage using FmocKyn(CHO,Boc)OH as a building block either in solution or on a solid support. Hence they resorted to a 12-step solution-phase synthesis of a branched tetrapeptide, during which formation of the ester linkage between Thr4 and Kyn13 was accomplished by ozonolyis of a suitably protected Trp residue.…”
mentioning
confidence: 99%